Assessing the Respect and Dignity for Human Life in the Nigerian Health Sector - Marcus Garvey Orji; Felicia Onyenemerem (Budapest International Research and Critics University, 2020)
Human dignity is ‘an individual or group's sense of self-respect and self-worth, physical and psychological integrity and empowerment. The basis for the theme of Human dignity, is that humans were created in the image and likeness of God. Regardless of any factors or reasons we can think of, individuals have an inherent and immeasurable worth and dignity; each human life is considered sacred and must be respected. Thus, the health sector has the obligation of considering the ethical dimensions of the major determinants of human health, respect and dignity. The objective of this study is to examine the issues of respect and dignity for human life in the Nigerian health sector. The study is a survey research, and data was collected from both primary and secondary source, and analysed by simple percentages and tabulations. The result of the findings revealed that respect and dignity for human life in the Nigerian health sector is very necessary; promotion and protection of human rights and of health care are fundamentally linked; Nigerian health workers have not fared well in the area of respect for human dignity, and that Nigerian government policies and cultures have impeded the protection of rights and dignity of persons in the health sector. The study among others recommended the education and change of mentality through media of the Nigerian health workers on the need for respect and dignity of human life in the health care institutions, reformation of the health care sector, planning it in such a way that respect and dignity for human life will reflect in the centrality of the programme of reformation and activities.